Food taboo for pregnant and lactating mothers: A study on indigenous peoples in South Sulawesi - Nurbaya Nurbaya; Yudianti Yudianti; Hapzah Hapzah; Najdah Najdah; Zaki Irwan; Juhartini Juhartini; Icha Dian Nurcahyani (AcTion: Aceh Nutrition Journal, 2024)
Indigenous people believe in and practice food taboos as part of traditional culture. Food taboos are associated with cultural beliefs and are passed on to every generation, particularly pregnant and lactating women. Food taboos in the Ammatoa Kajang and Kaluppini indigenous communities are specific to pregnant and lactating mothers. This study aimed to explore traditional knowledge and food taboos concerning maternal health among indigenous people in South Sulawesi. This study uses a qualitative method with purposive sampling. Data collection used in-depth interviews (IDIs) and focus group discussion (FGDs) guidelines. This study was conducted in Bulukumba, Enrekang Regency, South Sulawesi Province, from November 2017 to June 2018. The informants were mothers of children under five years, traditional birth attendants (TBAs), local midwives, and customary leaders. The data were analyzed in three categories:  coding process, categorization, and theme generation using Dedoose. We found that these two communities believed in and practiced food taboos that could prevent them from consuming various nutritious foods that are important during pregnancy and lactation. In conclusion, food taboos were practiced by both indigenous mothers, which may have prevented individuals from ingesting a variety of nutrient-dense foods that are crucial during nursing and pregnancy.Keywords: Belief, qualitative study, nutrition, taboo